Prognostic implication of HSPA (HSP70) in breast cancer patients treated with neoadjuvant anthracycline-based chemotherapy - Nadin, Silvina Beatriz (2013)
Neoadjuvant chemotherapy is used in patients with locally advanced breast cancer to reduce the tumor size before surgery. Unfortunately, resistance to chemotherapy may arise from a variety of mechanisms. The heat shock proteins (HSPs), which are highly expressed in mammary tumor cells, have been implicated in anticancer drug resistance. In spite of the widely described value of HSPs as molecular markers in cancer, their implications in breast tumors treated with anthracycline-based neoadjuvant chemotherapy has been poorly explored. In this study, we have evaluated by immunohistochemistry the expression of HSP27 (HSPB1) and HSP70 (HSPA) in serial biopsies from locally advanced breast cancer patients (n= 60) treated with doxorubicin (DOX) or epirubicin (EPI) based monochemotherapy. The serial biopsies were taken at days 1, 3, 7, 21, and compared with the pre-chemotherapy and the surgical biopsies. After surgery the patients received additional chemotherapy with Cyclophosphamide, Methotrexate and 5-Fluorouracil (CMF). High nuclear HSPB1 and HSPA expressions were found in invasive cells after DOX/EPI administration (P<0.001), but the drug did not affect the cytoplasmic expression of the HSPs. Infiltrating lymphocytes showed high nuclear HSPA (P<0.01) levels at post-chemotherapy. No correlations were found between HSPs expression and the clinical and pathological response to neoadjuvant therapy. However, in the post-chemotherapy biopsies, high nuclear (>31% of the cells) and cytoplasmic HSPA expressions (>11% of the tumor cells) were associated with better DFS (P=0.0348 and P=0.0118, respectively). We conclude that HSPA expression may be a useful prognostic marker in breast cancer patients treated with neoadjuvant DOX/EPI chemotherapy, indicating the need to change the administered drugs after surgery for overcoming drug resistance.